2022
DOI: 10.1002/jper.21-0494
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of GCF IL‐17, IL‐10, TWEAK, and sclerostin levels after scaling and root planing and adjunctive use of diode laser application in patients with periodontitis

Abstract: Background The aim of the present study was to evaluate the clinical efficacy of the diode laser as an adjunct to scaling and root planing (SRP) and also determine the biochemical profile by evaluating the gingival crevicular fluid (GCF) levels of interleukin (IL)‐17, IL‐10, tumor necrosis factor‐related weak inducer of apoptosis (TWEAK), and sclerostin. Methods A total of 40 systemically healthy, patients with Stage III periodontitis were included in this randomized controlled study. Participants were randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 48 publications
1
17
0
1
Order By: Relevance
“…No significant differences between healthy and periodontitis sites were found in only one study 51 . When the correlation between SOST and clinical parameters was evaluated, significant positive findings were identified in five investigations 45,47,48,50,57 . With respect to Wnt5a, the expression of Wnt5a mRNA was significantly higher in periodontitis in two publications 55,56 .…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…No significant differences between healthy and periodontitis sites were found in only one study 51 . When the correlation between SOST and clinical parameters was evaluated, significant positive findings were identified in five investigations 45,47,48,50,57 . With respect to Wnt5a, the expression of Wnt5a mRNA was significantly higher in periodontitis in two publications 55,56 .…”
Section: Resultsmentioning
confidence: 90%
“…The follow‐up time ranged from 1 week to 3 months. The levels of SOST showed a significant decrease at 6 weeks 45 and 3 months 47,48 following non‐surgical periodontal treatment, while one study found no significant difference was found at 1‐month post‐treatment 47 . Therefore, during the early healing phase (≤30 days), the change in the SOST concentration was not significant, however reached significance at the late phase following periodontal treatment.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations